Polygonum anatolicum (Polygonaceae): a new unique species from Türkiye - Eker, İsmai̇l; Keski̇n, Mustafa (Phytotaxa, 2025)
Polygonum is a taxonomically complex genus comprising more than 173 species. The flora of Türkiye includes 34 species of Polygonum, 13 of which are endemics (two are annuals, eleven are perennials). Based on field surveys in southern Türkiye, as well as examination of specimens deposited in various herbaria, we here propose to described a new species for science, Polygonum anatolicum. This species is an annual with extremely slender stems, and can be easily distinguished from other annuals knotweeds by its zig-zag twisting, especially at the end of the branches, tiny flowers, and quickly shed basal and tiny leaves. With the new species in this article, the number of Polygonum species in Türkiye has increased to 35 and the number of endemic taxa to 14.